PsycEXTRA Dataset 2011
DOI: 10.1037/e653632011-036
|View full text |Cite
|
Sign up to set email alerts
|

Sex and performance under competition: Is there a stereotype threat shadow?

Abstract: In this paper we experimentally study performance of men and women under competition, with implicitly and explicitly induced stereotype threats to both sexes. We use a mathematical task that is perceived as male-dominant and creates an implicit stereotype threat against woman. We also study conditions in which we explicitly reinforce or contradict the implicit stereotype threat by providing appropriate information. We find that despite stereotype threats against women, both men and women react positively and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…12 In short, we consider that it is rational for participants to provide their best effort regardless of their choice of x. Following Geraldes, Riedl, and Strobel (2017), we use participants' number of attempts to tackle the addition problems as a proxy measure of effort provision. In Table 4.8, we see that participants in the GM condition significantly increase their number of attempts to solve the addition problems in the competitive round.…”
Section: Effort Provisionmentioning
confidence: 99%
“…12 In short, we consider that it is rational for participants to provide their best effort regardless of their choice of x. Following Geraldes, Riedl, and Strobel (2017), we use participants' number of attempts to tackle the addition problems as a proxy measure of effort provision. In Table 4.8, we see that participants in the GM condition significantly increase their number of attempts to solve the addition problems in the competitive round.…”
Section: Effort Provisionmentioning
confidence: 99%
“…It has been shown that competition varies across age (Gneezy and Rustichini, 2004;Flory et al, 2018;Mayr et al, 2012), different cultural backgrounds (Gneezy et al, 2009;Andersen et al, 2013;Leibbrandt et al, 2013;Dariel et al, 2017), and gender (Croson and Gneezy, 2009;Niederle and Vesterlund, 2011;Niederle, 2015). In addition, exogenous factors such as stereotype-threat in the task and the group composition (e.g., number of competitors, gender composition and the existence of information contradicting an existing stereotype) can shape competitive behavior (Gneezy et al, 2003;Booth and Nolen, 2009;Geraldes et al, 2011;Iriberri and Rey-Biel, 2012;Dreber et al, 2014;Jung and Vranceanu, 2017).…”
Section: Introductionmentioning
confidence: 99%